2015
DOI: 10.1016/j.chemgeo.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Transformations from triclinic to hexagonal birnessite at circumneutral pH induced through pH control by common biological buffers

Abstract: Laboratory experiments that explore the bioprecipitation or redox transformations of layered Mn oxides commonly employ buffers, such as the HEPES and MES buffers, to maintain solution pH to near neutrality. The assumption is that holding solution pH constant does not serve as the primary control for the variety of Mn oxide produced. To test this assumption, synthetic triclinic Na-birnessite was reacted in batch experiments with a pH 7 HEPES buffer, a pH 7 MES buffer, and an unbuffered pH 7 solution for 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
1
13
1
Order By: Relevance
“…One recent study, however, observed that TriB partially transforms to hexagonal H-birnessite at 573 pH 7 in solutions containing 20 mM MES or HEPES buffers and in unbuffered solutions after 14 574 days (Ling et al, 2015). This distinct outcome compared to the present study and prior research 575 Silvester et al, 1997;Lanson et al, 2000) is of unclear origin.…”
contrasting
confidence: 90%
“…One recent study, however, observed that TriB partially transforms to hexagonal H-birnessite at 573 pH 7 in solutions containing 20 mM MES or HEPES buffers and in unbuffered solutions after 14 574 days (Ling et al, 2015). This distinct outcome compared to the present study and prior research 575 Silvester et al, 1997;Lanson et al, 2000) is of unclear origin.…”
contrasting
confidence: 90%
“…1b). These differences in Mn valence states and vacancy concentrations are integral in establishing their stability with respect to pH and in predicting their chemical reactivity in natural environments (Ling et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the primary buildup of Mn(III), which leads to passivation of the surface, results from the comproportionation reaction between Mn(II) product and surface Mn(IV) to produce Mn(III) [ 54 , 55 ]. This increase in Mn(III) is evidenced by the transformation of triclinic birnessite to hexagonal birnessite (Additional file 1 : Figure S6) [ 56 ], which is caused by migration of Mn(III) within the sheet to the interlayer region [ 39 ]. The oxidation of As(III) by surface Mn(III) is considered to be slow, consistent with the decreasing rate of As(V) formation as the reaction time increases [ 23 , 51 ].…”
Section: Resultsmentioning
confidence: 99%